A Simple Monetary Model of a Shortage Economy - Lin, Shoukang (IMF Working Papers; Working Paper ;, 1992)
During the transition from a centrally planned economy to a market economy, many countries seem to have experienced some degree of macroeconomic instability. This paper attempts to provide a theoretical explanation of this phenomenon. The paper develops a simple monetary model and shows how macroeconomic stability can be achieved in a rigid centrally planned economy, despite the inherent structural imbalances and irrational price system. On the other hand, the study shows that without hardening enterprise budget constraints, wage and price decontrol tends to destablize the economy and may lead to persistent budget deficits and inflation. The paper also provides a rigorous analysis of household savings and money demand in a shortage economy, and clarifies the somewhat confusing concept of 'monetary overhang' in the literature.